Monitoring of overtraining and motivation in elite soccer players - Leonardo Henrique Silva Fagundes; Israel Teoldo da Costa; Cleiton Pereira Reis; Guilherme de Sousa Pinheiro; Varley Teoldo Costa (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: This study aimed to monitor the behavior of the overtraining and motivations dimensions, as well as to verify whether these dimensions correlate in the preparatory and competitive periods over the season. Methods: Professional soccer players (n = 32) answered the Stress and Recovery Questionnaire for Athletes (RESTQ-Sport 76) and the Sport Motivation Scale (SMS) during the preparatory and competitive periods. Results: Intrinsic amotivation and sport-specific recovery were lower in the competitive period than in the preparatory period. In the preseason, motivation presented a strong and negative correlation with overall recovery (p = 0.001; r = −0.75; r2 = 0.56) and sport-specific recovery (p = 0.001; r = −0.72; r2 = 0.52). The amotivation explained in 56% the variance of the results of the overall recovery and 52% of the sport-specific recovery. During the competitive phase, amotivation showed a strong and positive correlation with overall stress (p = 0.001; r = 0.70; r2 = 0.49) and sport-specific stress (p = 0.001; r = 0.79; r2= 0.62). The amotivation accounted for 49% of the variance in the results of the overall stress and 62% of sport-specific stress in soccer players. Conclusion: There are associations between overtraining and motivation during the investigated periods. Through longitudinal monitoring in professional soccer, it was verified that the dimensions of amotivation, overall recovery, and sport-specific stress could be related to the prevention symptoms of overtraining in a professional soccer team.